The Impact of Psychological Capital on Job Burnout of Chinese Nurses: The Mediator Role of Organizational Commitment - Peng, Jiaxi (Public Library of Science, 2013)
BACKGROUND: Nursing has a high risk of job burnout, but only a few studies have explored its influencing factors from an organizational perspective. OBJECTIVE: The present study explores the impact of psychological capital on job burnout by investigating the mediating effect of organizational commitment on this relationship. METHODS: A total of 473 female nurses from four large general hospitals in Xi’an City of China were selected as participants. Data were collected via the Psychological Capital Questionnaire, the Maslach Burnout Inventory-General Survey, and the Organizational Commitment Scale. RESULTS: Both psychological capital and organizational commitment were significantly correlated to job burnout. Structural equation modelling indicated that organizational commitment partially mediated the relationship between psychological capital and job burnout. CONCLUSION: The final model revealed a significant path from psychological capital to job burnout through organizational commitment. These findings extended prior reports and shed some light on the influence of psychological capital on job burnout.